Pengaruh ekstrak bawang putih terhadap pertumbuhan setek batang pada berbagai jenis bugenvil (Bougainvillea spectabilis Willd) - Dessy Dora Meidodga; Florentina Heningtyas Listyorini; Theresia Tan; Linda Ernawati Lindongi (Agrotek, 2021)
This research aimed to study the effect of garlic extract on the growth of stem cuttings of several types of bougainvillea and used a factorial randomized block design (RAK) with two factors. First factor is garlic extract in 2 levels, (with or without garlic extract). Second factor 2 is the type of bougainvillea consisting of 5 varieties such as yellow flowers, dark purple flowers, white flowers, red flowers and orange flowers. The results showed that the interaction between onion extract and bougainvillea had no significant effect on all observed variables (sprouting time, number of shoots, shoot length, number of roots, root length, percentage of cuttings sprouted and percentage of rooted cuttings). Garlic extract had no significant effect on all observed variables. There was a tendency for cuttings given garlic extract to show a faster age of budding, more shoots, longer roots and more roots. The type of bougainvillea gave a very significant effect on all observed variables except the number of shoots. Red flowers show the earliest age to start sprouting (16.80 days), the longest shoots (26.03 cm) and the longest roots (9.43 cm). Orange flowers performed the highest number of shoots (4.79), the highest percentage of shoots (96.67%) and the highest percentage of roots (96.67). Yellow flowers showed the latest sprouting time (37.08 days), the shortest shoot length (2.51 cm), the shortest root length (1.56 cm), and the least number of roots (1.06). Dark purple flowers showed the lowest percentage of budding and root percentage (63.33%).